Highly efficient photoelectrochemical and photocatalytic anodic TiO2 nanotube layers with additional TiO2 coating. (December 2017) - Sopha, Hanna; Krbal, Milos; Ng, Siowwoon; Prikryl, Jan; Zazpe, Raul; Yam, Fong Kwong; Macak, Jan M.
Graphical abstract: Highlights: Self-organized TiO2 nanotube layers were coated with additional TiO2 layers by ALD. These coatings passivated surface defects on TiO2 nanotube walls. Highly efficient charge carrier separation was achieved upon UV light illumination. This was translated in strongly enhanced photo-electrochemical response. Significant enhancement of photocatalytic decomposition rates for methylene blue. Abstract: In this work, strong beneficial effects of thin and uniform TiO2 coatings within TiO2 nanotube layers for photocurrent generation and photocatalytical degradation of methylene blue are demonstrated for the first time. TiO2 nanotube layers were coated by TiO2 of various thicknesses (from 2.8 nm to 22 nm) using atomic layer deposition (ALD) and compared with TiO2 nanotube layers decorated by TiO2 nanoparticles (using established TiCl4 treatment) and with blank (uncoated) layers. By means of photocurrent measurements and cyclic voltammetry, it is demonstrated that the most efficient charge carrier separation can be achieved for TiO2 nanotube layers with an optimal ALD TiO2 coating thickness ≈11 nm. Significant differences in flatband potentials and carrier density among all nanotube layers were revealed by Mott-Schottky measurements. Photocatalytic decomposition rates for methylene blue solutions were significantly enhanced for ALD TiO2 coated TiO2 nanotube layers compared to their uncoated or TiO2 nanoparticles - decorated counterparts. A perfect agreement in trends was obtained for photocurrent and photocatalytic results.